Current Epidemiological Features of Viral Hepatitis B and C, Tuberculosis and HIV Infection In Psychiatric Hospitals - A. A. Asratyan (Журнал микробиологии, эпидемиологии и иммунобиологии, 2020)
Background. Psychiatric hospitals, where patients with immunodeficiency often do not comply with basic preventive measures, as well as receiving a wide range of medical procedures, including parenteral ones, are the institutions of high risk of socially significant infections spreading.The aim was to study the current epidemiological features of parenteral hepatitis among various categories of mentally ill patients (with pulmonary tuberculosis and HIV infection) and medical personnel in a large psychiatric hospital.Materials and methods. Serological markers of hepatitis B (HB) and hepatitis C (HC) were determined in 8352 patients and 542 employees of a large psychiatric hospital using domestic diagnostic test systems.Results. Markers of HB and HC among patients were revealed in 7.2% of persons (HB — 2.8%, HC — 3.1%, and HB+HC — 1.4%). The analysis of sex, age and social characteristics of HBVand HCV-patients was conducted. Markers of HC were significantly more common in HIV-infected patients (44.4% of individuals); the main routes of transmission of HB and HC were intravenous drug use and sexual intercourse. Among patients with pulmonary tuberculosis, the maximum number of persons was found with markers of HB (44.3%) and HB+HC (38.2%); the main clinical form of pulmonary tuberculosis was represented by the infiltrative form (60.4%); in 53,7% of cases the bacillary forms were identified that pose a serious epidemiological risk in the spread of tuberculosis in the hospital. Analysis of the social structure showed that HBV+HC+HIV and pulmonary tuberculosis are characteristics of persons with aggravated social status. The most frequent factors of infection with HBV and HCV were longterm parenteral loading and intravenous drug use. The greatest factor of parenteral load was observed in mentally ill patients diagnosed with HB+HC accompanying tuberculosis. It was shown that the frequency of HBV and HCV markers detection among medical personnel depends on the department profile, work duration, frequency and risk of contact with blood during professional activity.Conclusion. A high level of comorbidity of mental disorders and socially significant infectious diseases (HIV infection, tuberculosis and HB and HC) has been established, which has a significant impact on the epidemic process of these infections. Preventive programmes established in hospitals and in the territories they serve should take into account their comorbidity. The necessity of specific and non-specific prevention of viral hepatitis in patients and medical staff of psychiatric hospitals is shown.